Breeding dynamics of a Golden Eagle (Aquila chrysaetos) population in the boreal forest of Sweden - Daouti, Eirini - Lamprini (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2017)
Successful conservation and management of Golden Eagle (Aquila chrysaetos) requires an in-depth understanding of its’ demographic parameters. The species in Sweden is listed as Near Threatened and threats include increasing demands for renewable energy, collisions with railways, illegal persecution, and lead poisoning. Breeding performance and survival estimates can be used to increase the knowledge of the population dynamics of this apex predator. I estimated breeding performance of Golden eagles by using citizen science data from 44 territories in Northern Sweden from 1995 to 2015.Ring recovery data from the National ringing database of the Stockholm museum of Natural history, were used to estimate population and age-specific survival. Weather, voles’ density and topographic variables incorporated to Generalized Linear Mixed Models (GLMMs) to explain the patterns of breeding success. In continue, fecundity and survival estimates used to structure a stage-structured Lefkovitch population projection matrix to estimate population growth, stable stage distribution and elasticities and sensitivities of the growth rate. Long term population fecundity was estimated to be 0.51 (young per pair) and breeding success it is likely to be affected by vole index, snow depth and precipitation preceding the breeding period and average temperature during the breeding. The best approximating model explained the 29% of the total breeding variance, which questions the size of the effect of habitat features and human-induced disturbance to Golden Eagles reproductive performance. Survival rates were similar with those reported in the U.S. with older individuals exhibiting higher survivorship (0.89) from the first age class (0.79). The population exhibits a positive growth rate (1.1) while elasticities and sensitivities of the growth rate indicate that the most influential transition for the population growth is the one from 3 years old to 4 years old, while individuals older than 4 years old contribute more to population growth.